Early Modern Fire : Science, Technology, and the Urban Space - Bernasconi, Gianenrico,; Storni, Marco, (Early Modern History and Modern History E-Books Online, Collection 2024., 2025)
Early Modern Fire offers new perspectives on the history of fire in early modern Europe (ca. 1600-1800). Far from the background role that scholarship has traditionally assigned to fire, the essays in this volume demonstrate its centrality to understanding the entangled histories of science, technology, and society in the pre-industrial period. Analysing case studies ranging from alchemy to cooking, from firefighting to fireworks, the contributors show that the history of fire is not only one of change and progress, but also of continuity, characterised by the persistence of traditional know-how, small-scale innovation, and the coexistence of different paradigms. Contributors include: Gianenrico Bernasconi, Catherine Denys, Hannah Elmer, Liliane Hilaire-Pérez, Olivier Jandot, Cyril Lacheze, Andrew M.A. Morris, Cornelia Müller, Bérengère Pinaud, Stefano Salvia, Marco Storni, Marie Thébaud-Sorger, and Simon Werrett See Less